Pretreatment Eosinophil Counts in Patients With Advanced or Metastatic Urothelial Carcinoma Treated With Anti-PD-1/PD-L1 Checkpoint Inhibitors. Issue 7 (September 2021) - Mota, Jose Mauricio; Teo, Min Yuen; Whiting, Karissa; Li, Han A.; Regazzi, Ashely M.; Lee, Chung-Han; Funt, Samuel A.; Bajorin, Dean; Ostrovnaya, Irina; Iyer, Gopa; Rosenberg, Jonathan E.
Abstract : Eosinophils influence antitumor immunity and may predict response to treatment with immune checkpoint inhibitors (ICIs). To examine the association between blood eosinophil counts and outcomes in patients with advanced or metastatic urothelial carcinoma (mUC) treated with ICIs, we identified 2 ICI-treated cohorts: discovery (n=60) and validation (n=111). Chemotherapy cohorts were used as comparators (first-line platinum-based chemotherapy, n=75; second-line or more pemetrexed, n=77). The primary endpoint was overall survival (OS). Secondary endpoints were time on treatment (ToT) and progression-free survival. Univariate and multivariate analyses were performed using Cox proportional hazard models. Associations between changes in eosinophil count at weeks 2/3 and 6 after the start of ICI treatment were analyzed using landmark analyses. Baseline characteristics of the ICI cohorts were similar. In the discovery cohort, an optimal cutoff for pretreatment eosinophil count was determined [Eos-Lo: <100 cells/µL; n=9 (15%); Eos-Hi: ≥100 cells/µL; n=51 (85%)]. Eos-Lo was associated with inferior outcomes [OS: hazard ratio (HR), 3.98; 95% confidence interval (CI), 1.85–8.56; P <0.013; ToT: HR, 2.45; 95% CI, 1.17–5.10; P =0.017]. This was confirmed in the validation cohort [Eos-Lo: n=17 (15%); Eos-Hi: n=94 (85%)] (OS: HR, 2.51; 95% CI, 1.31–4.80; P =0.006; ToT: HR, 2.22; 95% CI, 1.2–3.80; P =0.004), and remained significant after adjustment for other prognostic factors. Changes in eosinophil counts at weeks 2/3 and 6 were not clearly associated with outcomes. In chemotherapy cohorts, eosinophil counts were not associated with outcomes. In conclusion, low pretreatment eosinophil count was associated with poorer outcomes in patients with mUC treated with ICIs, and may represent a new predictive biomarker. Abstract : Supplemental Digital Content is available in the text.